Kids at risk: children’s employment in Hazardous occupations in Brazil - Deborah S. DeGraff (Universidade de São Paulo, 2014)
While the literature on child labor in Brazil is large, it is not comprehensive:  in particular, there are few studies on children’s work in risky occupations, and those that exist tend to be qualitative and based on limited samples.  In this paper, we aim to paint a broader picture of children’s engagement in risky labor force work, based on quantitative evidence from PNAD data. We document associations between parental characteristics and children’s work, using both descriptive statistics and multivariate modeling to understand the determinants of child participation in risky labor force work. Brazilian children engaged in risky occupations are less likely than even other employed children to be enrolled in school, and more likely to work long hours and experience a variety of working conditions that may be unsafe.  We also see that there are likely to be vast differences between girls and boys in their experience working in hazardous occupations, and that girls are over-represented in risky jobs in Brazil.